2017
DOI: 10.1038/s41598-017-06258-0
|View full text |Cite
|
Sign up to set email alerts
|

3D anatomical and perfusion MRI for longitudinal evaluation of biomaterials for bone regeneration of femoral bone defect in rats

Abstract: Magnetic Resonance Imaging (MRI) appears as a good surrogate to Computed Tomography (CT) scan as it does not involve radiation. In this context, a 3D anatomical and perfusion MR imaging protocol was developed to follow the evolution of bone regeneration and the neo-vascularization in femoral bone defects in rats. For this, three different biomaterials based on Pullulan-Dextran and containing either Fucoidan or HydroxyApatite or both were implanted. In vivo MRI, ex vivo micro-CT and histology were performed 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…A homogenous seeding of MC3T3-E1 cells within the pore network was achieved by the simple addition of a cell suspension on freeze-dried scaffolds. Isolated cells of different origins (species, tissues), two or more cell types, or cell clusters can be accommodated in these 3D porous scaffolds [17][18][19]21]. Such scaffolds are suitable for cell culture in 3D (especially when cell clustering and spheroid growth is necessary for studying cell development and differentiation), for tissue engineering or for pharmacological assays in 3D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A homogenous seeding of MC3T3-E1 cells within the pore network was achieved by the simple addition of a cell suspension on freeze-dried scaffolds. Isolated cells of different origins (species, tissues), two or more cell types, or cell clusters can be accommodated in these 3D porous scaffolds [17][18][19]21]. Such scaffolds are suitable for cell culture in 3D (especially when cell clustering and spheroid growth is necessary for studying cell development and differentiation), for tissue engineering or for pharmacological assays in 3D.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we address the mechanisms of pore formation by freeze-drying in a polysaccharide-based hydrogel scaffold designed for bone tissue engineering [16]. This biomaterial is under research and industrial developments [17][18][19][20][21]. The scaffolds are manufactured according to Route 1 with a low cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…It preserves the fracture side without opening of the trauma site, as it has to be performed when using plates or osteotomy models 14,15,19,24 . Some research groups investigating bone structures or bone healing in mice or rats already showed assessment of bone and surrounding tissues with MRI by 4,6,8,9,23,24 . In a recent study by Haffner-Luntzer et al 9 an external fixator was used in an osteotomy model of mice with ceramic mounting pins that allow MR-Imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, advanced imaging technologies like positron-emission-tomography combined with computed-tomography (PET/CT), microcomputer-tomography (µCT) and magnetic-resonance-imaging (MRI) are used frequently and contribute to a new understanding of bone tissue composition, regeneration and disease 1 3 . Technical progress with regard to increased resolution and the development of contrast agents and labeling techniques provides new insights also in small animal analysis of musculoskeletal tissues, now 4 6 . Zachos et al 7 , Malaval et al 8 and Taha et al 9 used non-invasive MRI and a bone quantification procedure to follow bone regeneration and healing in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there are a number of reports evaluating the bone-forming ability of biomaterials using rat models, such as bone defect in calvaria [1,29,33], jaw [39], and long bone [45]. Those defects were surgically created in pre-existing bone tissue.…”
Section: Discussionmentioning
confidence: 99%